E0201 Heat shock protein 90 protects rat mesenchymal stem cells against hypoxia and serum deprivationinduced apoptosis via PI3KAkt and ERK12 pathways. (17th November 2010) - Feng, Gao; Xinyang, Hu; Xiaojie, Xie; Qiyuan, Xu; Yaping, Wang; Xianbao, Liu; Meixiang, Xiang; Yong, Sun; Jian-an, Wang
Abstract : Objective: Mesenchymal stem cells (MSCs) transplantation has shown therapeutic potential to repair the ischaemic and infracted myocardium, but the effects are limited by apoptosis and loss of donor cells in host cardiac microenvironment. The aim of this study is to explore the cytopretection of Hsp90 against hypoxia and serum deprivation induced apoptosis and the possible mechanisms. Methods: Cell viability was determined by 3-(4.5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay. Apoptosis was assessed by Hoechest 33258 nuclear staining and flow cytometric analysis with annexin V/PI staining. The gene expression of TLR4 and ErbB2 was detected by real-time PCR. The protein levels of cleaved-caspase3, bcl-2, bcl-xL, bax, total-Erk, phospho-Erk, total-Akt, phospho-Akt and hsp90 were detected by western-blot. The production of nitric oxide was measured by spectrophotometric assay. Results: Hsp90 improves MSCs viability and protects MSCs against apoptosis induced by serum deprivation and hypoxia. The protective role of Hsp90 not only elevates bcl-2/bax and bcl-xL/bax expression but also decrease cleaved-caspase3 expression via down-regulating TLR-4 and ErbB2 membrane receptors. By binding to TLR-4 and ErbB2, Hsp90 activates the PI3K/Akt and ERK1/2 pathways. Hsp90 also down regulates the pro-apoptotic protein bax. It is demonstrated that exogenous Hsp90 elevates the expression levels of bcl-2/bax and bcl-xL/bax by activating the TLR-4 and ErB2 downstream PI3K/Akt and ERK1/2 pathways, which decreases cleaved caspase-3. Conclusion: Hsp90 significantly protects MSCs against apoptosis induced by hypoxia and serum deprivation. These findings demonstrates a novel and effective treatment strategy against MSC apoptosis in cell transplantation.